Patients undergoing invasive coronary angiography after a positive single-photon emission computed tomography or a positive stress cardiac magnetic resonance - What to expect at the cath lab. (13th July 2021) - Silva, C; Goncalves, M; Lopes, P; Ventosa, A; Calqueiro, J; Freitas, PN; Guerreiro, S; Brito, J; Abecasis, J; Raposo, L; Saraiva, C; Goncalves, PA; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Randomized controlled trials comparing stress cardiac magnetic resonance (CMR) and single-photon emission computed tomography (SPECT) suggest similar diagnostic accuracy for detecting obstructive coronary artery disease (CAD). However, there are few data on whether or not this remains true in routine clinical practice. The aim of this study was to assess the clinical and angiographic characteristics of patients undergoing invasive coronary angiography (ICA) after a positive stress CMR or positive SPECT, and to compare their positive predictive value with published results from the CE-MARC trial. Methods: In this retrospective tertiary-center analysis, we included 429 patients (mean age 67 ± 10 years, 28% women, 42% diabetic) undergoing ICA between January 2016 and December 2020, after a positive stress CMR or positive SPECT. Regarding stress test, an adenosine protocol was performed in all stress CMR and in 76.4% (n = 272) of stress SPECT. Stress test results, including ischemia location and severity, were classified as reported by their primary readers. Patients with missing data on key variables, and those in whom microvascular disease was considered likely in the original stress test report were excluded. Obstructive CAD was defined as any coronary artery stenosis ≥ 50% in a vessel compatible with the ischemic territory on stress testing. Results: Out of the total 429 patients, 356 (83%) were referred after a positive SPECT, and 73 (17%) after a positive stress CMR. Patients did not differ regarding age, cardiovascular risk factors, previous revascularization or left ventricular dysfunction, but patients with SPECT were more frequently male (p = 0.046). Overall, 320 patients (75%) had obstructive CAD on ICA. The prevalence of obstructive CAD was similar in patients with positive SPECT vs. positive stress CMR (76.1% vs. 80.8%, respectively, p = 0.385). There were also no significant differences in the prevalence of left main or 3-vessel disease (9.0% vs. 9.6%, p = 0.871, and 19.7% vs. 23.3% p = 0.483, respectively). Revascularization was performed or planned in 59.3% of patients in the SPECT group, and 52.1% of those in the stress CMR group (p = 0.255). The positive predictive values of both techniques were similar to those reported in the CE-MARC trial (Figure), and would increase to 88.1% and 89.4% for SPECT and stress CMR, respectively, if patients reported as having only mild ischemia were excluded. Conclusion: In this tertiary center analysis, stress CMR and SPECT showed similar positive predictive values, comparable to those reported in the CE-MARC trial.